[tex]a)\\\\ \frac{1}{a+1} +\frac{2}{a} =\frac{a+2(a+1)}{a(a+1)} =\frac{a+2 a+ 2}{a^2+a} =\frac{3a+ 2}{a^2+a} \\\\b)\\\\ \frac{1}{a+1} -\frac{ 1}{a+2} = \frac{a+2-(a+1)}{(a+1)(a+2)} =\frac{a+2- a-1}{ a^2+2a+a+2} =\frac{ 1}{ a^2+3a +2}[/tex]
[tex]c)\\\\ \frac{2p-1}{2p+1} -\frac{1}{2p} = \frac{2p(2p-1)-(2p+1)}{2p(2p+1)} = \frac{ 4p^2-2p- 2p-1}{4p^2+2p }= \frac{ 4p^2-4p-1}{4p^2+2p }\\\\d)\\\\ \frac{6k}{3k-1} +\frac{2k}{1-k} =\frac{6k(1-k)+2k(3k-1)}{(3k-1)(1-k)} =\frac{6k -6k^2+6k^2- 2k} {3k-3k^2-1+k}=\frac{4k } {-3k^2+4k-1}[/tex]
[tex]1)\ sprowadzamy\ do\ wspolnego\ mianownika\\\\2)\\\\wymnazamy\\\\3)\\\\redukujemy\ wyrazy\ podobne[/tex]